Mandatory acquisition of shares – procedure - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Company Act of Republic of Serbia includes mechanism for the mandatory acquisition of shareholdings of minority shareholders. Process of mandatory acquisition is initiated by principal shareholder who has at least 90% of share capital and at least 90% of votes. Mandatory acquisition of shares is based on a resolution of shareholders assembly that results in the transfer to principal shareholder shares of minority shareholders. The majority requirement for resolution is simple majority and principal shareholder may participate in passing the resolution. The importance of shareholders resolution is to enable minority protection because action for set aside resolution is available, except because of inadequacy of compensation. In that case minority shareholder may address the court to ascertain adequate compensation. Higher compensation awarded to one minority shareholder is applicable to all others minority shareholders.